Transplant Tolerance Induction in Newborn Infants: Mechanisms, Advantages, and Potential Strategies - Pan, Hua; Gazarian, Aram; Dubernard, Jean-Michel; Belot, Alexandre; Michallet, Marie-Cécile; Michallet, Mauricette (Frontiers in Immunology, 2016)
Although several tolerance induction protocols have been successfully implemented in adult renal transplantation, no tolerance induction approach has, as yet, been defined for solid-organ transplantations in young infants. Pediatric transplant recipients have a pressing demand for the elaboration of tolerance induction regimens. Indeed, since they display a longer survival time, they are exposed to a higher level of risks linked to long-term immunosuppression (IS) and to chronic rejection. Interestingly, central tolerance induction may be of great interest in newborns, because of their immunological immaturity and the important role of the thymus at this early stage in life. The present review aims to clarify mechanisms and strategies of tolerance induction in these immunologically premature recipients. We first introduce the discovery and mechanisms of neonatal tolerance in murine experimental models, and subsequently analyze tolerance induction in human newborn infants. Hematopoietic mixed chimerism in neonates is also discussed based on in utero hematopoietic stem cell (HSC) transplant studies. We then review the recent advances in tolerance induction approaches in adults, including the infusion of HSCs associated with less toxic conditioning regimens, regulatory T cells/facilitating cells/mesenchymal stem cells transplantation, costimulatory blockade, as well as thymus manipulation. Finally, IS withdrawal in pediatric solid organ transplant is discussed. In conclusion, the establishment of transplant tolerance induction in infants is promising and deserves further investigations. Future studies could focus on the selection of patients, on less toxic conditioning regimens, and on biomarkers for IS minimization or withdrawal.